XAS spectroelectrochemistry: reliable measurement of X‐ray absorption spectra from redox manipulated solutions at room temperature. (14th April 2016) - Best, Stephen P.; Levina, Aviva; Glover, Chris; Johannessen, Bernt; Kappen, Peter; Lay, Peter A.
Abstract : A room‐temperature flow in situ electrosynthesis cell suitable for X‐ray absorption spectroscopy with fluorescence detection is described. The small sample volume requirements and control over the solution flow profile make possible reliable measurements of photosensitive compounds and protein samples. Abstract : The design and operation of a low‐volume spectroelectrochemical cell for X‐ray absorption spectroscopy (XAS) of solutions at room temperature is described. Fluorescence XAS measurements are obtained from samples contained in the void space of a 50 µL reticulated vitreous carbon (sponge) working electrode. Both rapid electrosynthesis and control of the effects of photoreduction are achieved by control over the flow properties of the solution through the working electrode, where a good balance between the rate of consumption of sample and the minimization of decomposition was obtained by pulsing the flow of the solution by 1–2 µL with duty cycle of ∼3 s while maintaining a small net flow rate (26–100 µL h −1 ). The performance of the cell in terms of control of the redox state of the sample and minimization of the effects of photoreduction was demonstrated by XAS measurements of aqueous solutions of the photosensitive Fe III species, [Fe(C2 O4 )3 ] 3−, together with that of the electrogenerated [Fe(C2 O4 )3 ] 4− product. The current response from the cell during the collection of XAS spectra provides an independent measure of the stability of the sample of the measurement. The suitability of the approach for the study of small volumes of m M concentrations of protein samples was demonstrated by the measurement of the oxidized and electrochemically reduced forms of cytochrome c .